Angiographic findings of pulmonary arterial involvement in Behcet's Disease: Do they correlate with symptoms and acute phase response - KOCAKAYA, DERYA (My University, 2023)
Introduction: Behcet’s disease (BD) is a chronic inflammatory disorder with arterial vasculitis. Although, pulmonary artery aneurysm (PAA) is accepted as the prototypic arterial disorder, an increasing presence of pulmonary artery thrombosis (PAT) with or without aneurysms was also reported in recent studies. In this study, we aimed to describe computed tomography pulmonary angiography (CTPA) findings of pulmonary involvement and its correlation with symptoms and acute phase response in BD. Method: In this retrospective study, 153 CTPA of BD patients were assessed by two radiologists. Clinical and laboratory data were collected from the patient files. Pulmonary artery involvement (PAI) was defined as thrombus or aneurysm in CT angiography. Results: Most of (85.6 %) our patients were male and median age was 33.7 ± 10 years during angiographic assessments. Sixty-two (40.5 %) angiographies presented a thrombus: 14 subsegmental, 29 segmental, 13 lobar and 6 main branches. Among these, 82.3 % (n = 51) had bilateral involvement. Isolated PAT was present in 58 (93.5 %) angiographies with only 4 (2.6 %) angiographies displaying an aneurysm together with a thrombus. Pulmonary infarction was detected in 9 angiographies. Forty-four (29.3 %) patients, almost all of them under immunosuppressive treatments for other indications, were screened for asymptomatic pulmonary involvement (without any symptoms or increased acute-phase response (APR)), and one fourth of these were diagnosed as having a segmental or subsegmental PAT. Conclusion: Our results show that isolated pulmonary thrombosis is the main form of PAI, and isolated pulmonary aneurysm formation is rare in our BD cases. In the presence of pulmonary symptoms with or without increased APRs, involvement of segmental or more proximal parts of pulmonary arteries is most commonly detected. We also observed that PAI may be seen in about one fourth of especially male BD patients without symptoms or increased APR. Our results suggest that BD patients with pulmonary symptoms should be screened by CTPA for PAI, however, further research is needed to clarify the role of routine CTPA screening in asymptomatic BD patients.
Keywords: Acute phase reactants; Behcet’s disease; Pulmonary artery aneurysm; Thrombus